A Descriptive Study on Barriers to Reading English Texts and The Self-Directed Learning Method - Halim, Abdul; Khairun Nisa Kharisma (MAN Insan Cendekia Jambi, 2025)
The study aims to identify the English reading texts barriers faced by students of guidance and counselling department at PGRI University of Banyuwangi and to know the category level of self-directed learning method used by students of guidance and counselling department. Language barriers include barriers in understanding vocabulary, grammar, semantics, complexity of the reading text material, and decoding or word recognition. Meanwhile, psychological barriers involve issues such as lack of focus, forgetfulness, low self-confidence, shyness, and lack of motivation. These barriers are typically categorized into language and psychological barriers. These barriers hinder students’ ability to comprehend English texts effectively. To overcome these difficulties, many students adopt a self-directed learning (SDL) method, which enables them to take initiative in managing their learning process, including identifying personal learning goals, utilizing various resources, and evaluating their own progress. The research design was descriptive qualitative. The instrument used for data collection consist of 40 questions. The researcher found that there are 2 barriers in reading English text, namely language barriers and psychological barriers. In terms of language barriers, the researcher found that students have more barriers in understanding English grammar. Meanwhile, in psychological barrier, students have higher psychological barriers in felt shyness when reading English texts in front of others. In addition, in self-directed learning method students have more used medium level self-directed learning method.